Analisis Prediksi Keterlambatan Pembayaran Listrik Menggunakan Komparasi Metode Klasifikasi Decision Tree dan Support Vector Machine - Dinda Nabila Batubara; Agus Perdana Windarto; Eka Irawan (STMIK Budi Darma, 2022)
Electrical energy is one of the most needed energy today. In this modern era, almost all human activities cannot be separated from the use of electricity. The only electricity supply company in Indonesia is the State Electricity Company or PT. PLN (Persero). PLN also has several obstacles. One of them is the very large amount of arrears to customers. This causes considerable losses for PLN. The electricity payment counter also experienced the same thing as experienced by PLN, as at PT Jaya Nuhgra Pratama. For this reason, this research was conducted by comparing two methods in the classification, namely decision tree and support vector machine to find out which method is the best in solving problems and to find out the factors that are the main causes of delays in electricity payments